Pengaruh Tangibility, Reliability, Responsiveness, Assurance, Emphaty Dan Image Terhadap Customer Satisfaction pada PT. Bank Central Asia (BCA) Di Surabaya - Christin Verarika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine and analyze the effect of service quality, namely; tangible, reliability, responsiveness, assurance, empathy and image on customer satisfaction PT. Bank Central Asia (BCA) in Surabaya. This type of research is basic research using 6 research variables, namely tangibility, reliability, responsiveness, assurance, empathy and image. This study uses primary data by distributing questionnaires online. The sample used in this study were 320 respondents. While the data processing method in this study uses the IBM SPSS Statistic 24 software to test the validity and reliability test. While the method used for data processing is the SEM (Structural Equation Modeling) method with IBM AMOS 22.0 software to perform model tests (measurement models and structural models) and hypothesis testing. The results showed that the variables Tangibility, Assurance, Emphaty and Image have a significant positive relationship to Customer Satisfaction. Meanwhile, the Reliability and Responsiveness variables have a positive and insignificant relationship with Customer Satisfaction. Keywords: Service Quality, Customer Satisfaction, Image, Banking Service Quality